O cotidiano da morte e a secularização dos cemitérios em Belém da segunda metade do século XIX (1850/1891) - Silva, Erika Amorim da (2005)
This dissertation titled O cotidiano da morte e a secularização dos cemitérios em Belém na secunda metade do século XIX (1850/ 1891) tried to show understanding around death s meaning along with dead and mortuary ceremonies in Belém in the second half of the 19º century. Thus, the composition studies about the changes in the trip of death from the buries inside a church to open-sky cemeteries, plus the secularization of these spaces. Those questions have gained importance in the following pages cause they started a new parallel about the urban space threated by wide-spread diseases and miasmas exhalated from putrescent bodies. Taking that to explain the tensions formed in the core of Belém s society wich made same significant changes in the path of that specifical society before death and deads. The construction of the cemeteries- Nossa senhora da soledade and Santa Izabel - implacate in complex questios like start to bury dead bodies into open-sky cemeteries intead instead of inside churchs, the wish of the Catolic church to have exclusiveness in these new places, the secularization of those cemeteries and buries keeping in mind the unsolved religious, cultural and social conflicts to understanding the attitudes of the whites, indians, colored, catolics, protestants, masons and the way they used to react before the dead and death. So the city was visualized, it s quotidian and the existing and dying of it s inhabitants and seeing closest the representation before death and dead. To be well acquired with the text the central axel inquire the understanding of how different Belém s social divisions in the 80 s deal with circle of life including bury, mortuary ceremonies and the secularization of the cemeteries